1997
DOI: 10.1161/01.atv.17.4.646
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced Platelet Activation and Platelet Microparticle Formation at Blood Flow Conditions as in Arteries With a Severe Stenosis

Abstract: In the present study, we investigated whether high arterial shear stresses at various exposure times or a sudden increase in shear stress introduced by a stenosis affect platelet activation and platelet microparticle formation in native human blood. We used a parallel-plate perfusion chamber device through which nonanticoagulated human blood was drawn (10 mL/min) by a pump directly from an antecubital vein through the flow channel of a perfusion chamber at wall shear rates of 420, 2600, and 10500 s-1. In anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
293
0
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(318 citation statements)
references
References 37 publications
12
293
0
4
Order By: Relevance
“…Although it has been reported that shear stress causes activation of the platelet glycoprotein GPIIb-IIIa, 7 the effect of shear stress on GPIIb-IIIa could not be evaluated in the present study, since we did not measure GPIIb-IIIa activity. Instead, we measured ␤-thromboglobulin and platelet factor 4, which are constituents of the ␣-granule, as markers of platelet secretion.…”
Section: The Effect Of Shear Stress On Platelet Activitymentioning
confidence: 94%
See 1 more Smart Citation
“…Although it has been reported that shear stress causes activation of the platelet glycoprotein GPIIb-IIIa, 7 the effect of shear stress on GPIIb-IIIa could not be evaluated in the present study, since we did not measure GPIIb-IIIa activity. Instead, we measured ␤-thromboglobulin and platelet factor 4, which are constituents of the ␣-granule, as markers of platelet secretion.…”
Section: The Effect Of Shear Stress On Platelet Activitymentioning
confidence: 94%
“…[1][2][3][4][5][6] Shear stress has been considered an important promoter of adhesion and cohesion of platelets to endothelial cells activated by atherosclerosis. 7 The shear stress generated when blood flows through a vessel increases as blood flows rapidly through a stenosed artery, 8 which accelerates thrombus formation by activating platelets and inducing platelet adhesion and aggregation. [8][9][10] Most studies of platelet function, coagulation, and fibrinolysis in patients with ischemic heart disease have focused on acute coronary syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the sub-micron size of PMV, they may be able to withstand extreme shear stress, remaining in position to encourage further thrombus formation on extra-corporeal surfaces. 68 …”
Section: Adhesionmentioning
confidence: 99%
“…When considering the association of heart disease and platelet activation, an enlarged left atrium, endothelial damage, and the presence of mitral regurgitation all have the potential to generate high shear, resulting in platelet up‐regulation, release of alpha granule components, and increased sensitivity to agonists 15, 16. In vitro studies by Holme et al17 demonstrated shear‐induced platelet activation and development of platelet microparticles under flow conditions that may be similar to those associated with diastolic dysfunction in cats with HCM as suggested by Bedard et al 18…”
mentioning
confidence: 99%